2015
DOI: 10.1155/2015/761439
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Indoor Formaldehyde Decomposition Performance of Atmospheric Plasma Reactor Utilizing Sensor Network

Abstract: An experimental investigation is conducted into the indoor formaldehyde decomposition performance of an atmospheric plasma reactor with an airflow rate of 200 L/s, discharge power of 50 W, and operating voltage of 8.5 kV, utilizing a sensor network. It is shown that, given an initial formaldehyde concentration of ∼0.2 ppm, the reactor removes 15∼80% of the formaldehyde at a height of 107 cm and 20∼73% at a height of 180 cm after 5.5 hours. Moreover, it is shown that, in decomposing the formaldehyde, the reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Catalytic oxidation has been proved to be a useful method for degrading formaldehyde. It mainly includes photocatalytic oxidation (Sun et al, 2010;Dou et al, 2019), plasma technology (Saulich and Müller, 2013;Lo et al, 2015), thermal catalytic oxidation (Liu et al, 2019), and room-temperature catalysis (Wang et al, 2015). However, both photocatalytic oxidation and thermal catalytic oxidation use large-scale equipment, such as a heating unit and a light source.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic oxidation has been proved to be a useful method for degrading formaldehyde. It mainly includes photocatalytic oxidation (Sun et al, 2010;Dou et al, 2019), plasma technology (Saulich and Müller, 2013;Lo et al, 2015), thermal catalytic oxidation (Liu et al, 2019), and room-temperature catalysis (Wang et al, 2015). However, both photocatalytic oxidation and thermal catalytic oxidation use large-scale equipment, such as a heating unit and a light source.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the initial rapid adsorption of HCHO onto the TiO 2 photoreactor, the gaseous HCHO concentration jumps to the fixed value and the kinetic reaction is presumed as a first-order reaction (Langmuir isotherm). However, the results of data driven observation in most studies present an approximate zero-order reaction except for low concentration of HCHO (Lo et al, 2015;Yu et al, 2015). We suggest that the measurement uncertainties of rate-dependency are trade-off the accuracies of processing contributions in quantitation.…”
Section: Prediction and Large Scale Application Of The Box Modelingmentioning
confidence: 73%
“…Therefore, the aerosol term of HCHO is emphasized in our model to reflect the effect of water molecules in the photochemical reactions. Based on other studies (Han et al, 2012;Lo et al, 2015;Yu et al, 2015), three air conditions of temperature, relative humidity and wind speed are considered as the principal factors on the removal of gaseous VOCs indoors.…”
Section: Introductionmentioning
confidence: 99%
“…However in the case of ozone (O 3 ), previous experiments have shown that ozone production is significantly suppressed by VOC presence and weakly generated in ambient air alone at low supply voltage (1-3 kV) without addition of oxygen 11 . Shimizu 29 has shown that ozone production is significantly reduced by 54% in a microplasma DBD reactor operated by a Marx generator compared with a high voltage amplifier for indoor air cleaning, while Lo 19 reported that, using an atmospheric NTP reactor operated at 8.5 kV to decompose nearly 0.2 ppm formaldehyde, the ozone concentration evolved from the reactor was below detection limit (0.01 ppm). Additionally, the experimental results reported by Fan 15 vis-à-vis plasma-assisted ozone evolution mechanism studies indicate that outlet ozone reduces when air humidity increases, owing to the removal of •O by H 2 O to form •OH (Eq.…”
Section: Resultsmentioning
confidence: 99%